PENGARUH MEDIA "THE LINE FLASHCARD" TERHADAP KEMAMPUAN MENULIS AWAL ANAK USIA 4-5 TAHUN DI TK YAMASSA SURABAYA - Putri, Indy Alieffia (Jurnal Jendela Bunda Program Studi PG-PAUD Universitas Muhammadiyah Cirebon, 2023)
Fine motor potential in early childhood really needs to be developed considering the importance of having the ability to coordinate hand and eye muscles to carry out daily life. Observations made at TK Yamassa Surabaya show that there are still many children who have difficulty finding activities that require fine motor skills such as writing. This study uses a quasi-experimental research type with a non-equivalent control group design, which is a research design using pretest and posttest in the control group and the experimental group. Data collection techniques in this study were in the form of test techniques, observation or interviews, and documentation. Based on data analysis performed with SPSS 26 using the independent sample t test, the sig (2-tailed) result was 0.000<0.05, so Ha was accepted and H0 was rejected. The conclusion is that there is an influence of "The Line Flashcard" media on the early writing abilities of children aged 4-5 years. The researcher suggests that the teacher can use "The Line Flashcard" media for each child by printing A4 or A5 size, the teacher should use "The Line Flashcard" media with the classical method, but it is very necessary to do tests for each children so that the teacher knows the extent of the child's understanding of the concept of lines that have been taught.